MODERN METHODS FOR SOLVING FIRST-ORDER DIFFERENTIAL EQUATIONS - Jonqobilov Jahongir Tirkashevich (World Scientific Research Journal, 2025)
Abstract: First-order differential equations play a crucial role in mathematics, physics, engineering, and economics. This article examines modern methods for solving first-order differential equations, focusing on numerical techniques (e.g., Euler, Runge-Kutta), computational tools (e.g., MATLAB, Python), and machine learning-based approaches. The advantages, limitations, and practical applications of these methods are discussed. The aim of this study is to compare these methods, evaluate their effectiveness, and provide guidance for researchers and practitioners.